A novel intervals-based algorithm for the distribution short-circuit calculation - Obrenić, Marko Z.; Vidović, Predrag M.; Strezoski, Luka V. (Electrical engineering, 2019)
In this paper, a novel intervals-based distribution short-circuit calculation algorithm is proposed. In distribution networks, there are various renewable energy-based generators (solar panels, wind generators, small hydro turbines, etc.), as well as loads with uncertain generation and consumption. Therefore, short-circuit calculation has to consider all these uncertainties. The algorithm proposed in this paper deals with above-mentioned uncertainties, as well as correlations among them. Algorithm testing is performed on two test examples of distribution networks, 6-bus and 1003-bus, for the verification of its robustness and efficiency on real-life, large-scale systems. The results demonstrate that the proposed algorithm provides highly accurate results and that it is able to solve real-life short-circuit problems with a higher precision than the traditional deterministic short-circuit calculation algorithms.